Cross-border spillover: US gun laws and violence in Mexico - Arindrajit Dube; Oeindrila Dube; Omar García-Ponce (Institute for the Study of Labor (IZA), 2012)
To what extent, and under what conditions, does access to arms fuel violent crime? To answer this question, we exploit a unique natural experiment: the 2004 expiration of the U.S. Federal Assault Weapons Ban exerted a spillover on gun supply in Mexican municipios near Texas, Arizona and New Mexico, but not near California, which retained a pre-existing state-level ban. We find first that Mexican municipios located closer to the non-California border states experienced differential increases in homicides, gun-related homicides and crime gun seizures in the post-2004 period. Second, the magnitude of this effect is contingent on political factors related to Mexico's democratic transition. Killings increased substantially more in municipios where local elections had become more competitive prior to 2004, with the largest differentials emerging in high narco-trafficking areas. Our findings are consistent with the notion that political competition undermined informal agreements between drug cartels and entrenched local governments, highlighting the role of political instability in mediating the gun-crime relationship.
Keywords: K14; D72; D73; 330; gun control; violence; informal employment; cross-border spillover; cartels; Waffenrecht; Deregulierung; USA; Spillover-Effekt; Gewalt; Kriminalität; Organisierte Kriminalität; Mexiko